2001
DOI: 10.1159/000056889
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of HOX genes in the chicken genome reveals a new segment of conservation between human and chicken

Abstract: Homeobox genes play an important role in the regulation of early embryonic development. They represent a family of evolutionarily highly conserved transcription factors. In this work, several genes that belong to the four HOX gene clusters are assigned by in situ hybridization to four distinct chicken chromosomes. The four gene clusters are mapped to 2p2.1 (HOXA), 3q3.1 (HOXB), 1q3.1 (HOXC) and 7q1.3→ q1.4 (HOXD). We confirm partial homologies already detected by genetic mapping between chicken chromosomes 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
(24 reference statements)
0
4
1
Order By: Relevance
“…The linkage mapping for the INRA population shows the same association. This result contradicts a previous report based on fluorescent in situ hybridisation (FISH) that indicated that the HOXC cluster is located on chicken chromosome 1 and also the NCBI GenBank description about the position of chicken HOXC8 (Gene ID: 395711, at NW_003778389.1, from 237 bp to 1871 bp) [26]. We have also demonstrated that the Crest phenotype is associated with ectopic expression of HOXC8 in cranial skin during development which appears to be a reasonable explanation for the atypical feather growth on the heads of Crested chickens.…”
Section: Discussioncontrasting
confidence: 99%
“…The linkage mapping for the INRA population shows the same association. This result contradicts a previous report based on fluorescent in situ hybridisation (FISH) that indicated that the HOXC cluster is located on chicken chromosome 1 and also the NCBI GenBank description about the position of chicken HOXC8 (Gene ID: 395711, at NW_003778389.1, from 237 bp to 1871 bp) [26]. We have also demonstrated that the Crest phenotype is associated with ectopic expression of HOXC8 in cranial skin during development which appears to be a reasonable explanation for the atypical feather growth on the heads of Crested chickens.…”
Section: Discussioncontrasting
confidence: 99%
“…The genes for these orphan receptors are well conserved in the chicken, although human GPRC5A and GPRC5D may represent a duplication in mammals of GPRC5A/5D that we found in chicken. This scenario is also strengthened by their localization in close proximity on the human Chromosome 12p13.2–p13.1, which is a syntenic region to chicken Chromosome 1 where ggGPRC5A/D is positioned [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, although human/chicken comparative mapping has been well studied so far Ladjali-Mohammedi et al, 2001;Buitenhuis et al, 2002;Jennen et al, 2002Jennen et al, , 2003Nanda et al, 2002a;, RH-mapping data will increase the resolution of the gene maps within the conserved syntenies. It will thus help in refining the synteny breakpoints as well as detecting internal rearrangements, as it has been done in other species (Barbazuk et al, 2000;Goureau et al, 2001;Smith S.F.…”
Section: Construction Of the Gga10 Rh Mapmentioning
confidence: 99%